2018
DOI: 10.22201/ib.20078706e.2018.2.1921
|View full text |Cite
|
Sign up to set email alerts
|

Margay also hide their spots: first records of melanistic Leopardus wiedii from Colombia and Costa Rica

Abstract: Melanism has been commonly recorded in tropical felids, especially within the genus Leopardus. However, so far there are no reports of the existence of melanism in Leopardus wiedii. Herein, we present the first report of melanistic individuals of margays, obtained in Colombia and Costa Rica. The low frequency and scarcity of melanistic margay records along its distribution reflect that this is potentially not an ecological or adaptive advantage for the species, and likely the mutation is not established, or ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 6 publications
(7 reference statements)
0
7
0
Order By: Relevance
“…Of the six felid species that occupy Costa Rica, three are known to exhibit melanistic polymorphisms—jaguar ( Panthera onca ), jaguarundi ( Herpailurus yagouaroundi ), and northern tiger cat ( Leopardus tigrinus oncilla ); there are no records of melanistic puma ( Puma concolor ) or ocelot ( Leopardus pardalis ) in Costa Rica, and melanistic margay ( Leopardus wiedii ) have only recently been reported (González-Maya et al., 2018). It is reported that about 10% of jaguars globally are melanistic (Silva, 2017), and melanism in this species is inherited as a dominant trait caused by a 15-bp deletion in the MC1R gene that produces eumelanin in the background regions of the coat (Eizirik et al., 2003; Haag et al., 2010).…”
mentioning
confidence: 99%
“…Of the six felid species that occupy Costa Rica, three are known to exhibit melanistic polymorphisms—jaguar ( Panthera onca ), jaguarundi ( Herpailurus yagouaroundi ), and northern tiger cat ( Leopardus tigrinus oncilla ); there are no records of melanistic puma ( Puma concolor ) or ocelot ( Leopardus pardalis ) in Costa Rica, and melanistic margay ( Leopardus wiedii ) have only recently been reported (González-Maya et al., 2018). It is reported that about 10% of jaguars globally are melanistic (Silva, 2017), and melanism in this species is inherited as a dominant trait caused by a 15-bp deletion in the MC1R gene that produces eumelanin in the background regions of the coat (Eizirik et al., 2003; Haag et al., 2010).…”
mentioning
confidence: 99%
“…The hair is relatively short, thick, and soft. The species shows an extensive range of coloration, from a pale gray to ocher brown or cinnamon on the back, with shades that decrease in intensity ventrally (González-Maya et al 2018). From the ventral part of the mandible to the belly, the color is yellowish to white.…”
Section: Descriptionmentioning
confidence: 99%
“…The tail has about 12 dark-toned rings which do not completely close at the bottom (Reid 1997, de Oliveira 1998). Although rare, melanic individuals have been documented in Colombia and Costa Rica (González-Maya et al 2018).…”
Section: Descriptionmentioning
confidence: 99%
“…In México, there are records of margays in cloud forests for the states of Guerrero, Jalisco, Morelos, Oaxaca, and San Luis Potosí, at elevations between 800 and 2,750 m (Aranda et al 2012;Carvajal-Villarreal et al 2012;Cinta-Magallón et al 2012;Almazán-Catalán et al 2013;Aranda and Valenzuela-Galván 2015). In Costa Rica and Colombia, this cat was documented at altitudes of 1,529 and 2,313 m, respectively (González-Maya et al 2018).…”
mentioning
confidence: 99%